2022
DOI: 10.1007/s11846-022-00598-6
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization?A Matter of Trust: A Double-Mediation Model Investigating Employee Trust in Management Regarding Digitalization

Abstract: The purpose of this paper is to determine how employee trust in management regarding digitalization (TMD) is encouraged to successfully promote technological change linked to digitalization and implement digital technologies within organizations. TMD is considered a necessary precondition for employee cooperation regarding the successful implementation of digitalization within organizations. Derived from existing theoretical and empirical research on trust, a double-mediation model is developed. The proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…The top reasons for a common attribute like "conditional" and "unconditional" or "strong" and "weak" does not attract it (Innocenti, Pilati, & Peluso, 2011). The payoff has a higher influence on interaction behavior such as trust (Lau & Höyng, 2023). Researchers concluded that trust is influenced by compensation structures and that the impact of reward systems on trust is skewed by employee expectations as well as their colleague's trustworthiness (Men, Yue, & Liu, 2020).…”
Section: The Moderating Role Of Employee Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…The top reasons for a common attribute like "conditional" and "unconditional" or "strong" and "weak" does not attract it (Innocenti, Pilati, & Peluso, 2011). The payoff has a higher influence on interaction behavior such as trust (Lau & Höyng, 2023). Researchers concluded that trust is influenced by compensation structures and that the impact of reward systems on trust is skewed by employee expectations as well as their colleague's trustworthiness (Men, Yue, & Liu, 2020).…”
Section: The Moderating Role Of Employee Trustmentioning
confidence: 99%
“…The production capacity of such employees is high and they are more active in helping others (Top, Akdere, & Tarcan, 2015). Most companies focus on the labor's input in determining firms' performance but we are discussing the Employee's trust in the organizations because, without trust, organizations cannot enhance their performance and productivity (Lau & Höyng, 2023). A company that can build a strong feeling of trust in the workplace is better able to withstand the storms of competition and have a clear vision of what it stands for.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of information technology (IT) application in business management continues to grow, with digital technologies driving digitalization (Bouncken et al 2021a, b). For instance, Legner et al (2017) and Tilson et al (2010) argue that digitization refers to the adaptation and utilization of digital technologies in an organizational setting (Lau and Höyng 2023). These technologies transform traditional processes into digital ones within organizations (Bouncken et al 2021a, b).…”
Section: Introductionmentioning
confidence: 99%
“…For the last two decades, the field of technologies Information and Communication (TIC) advanced for opening a break-grounding change in business and management (Kraus et al, 2022;Lau and H€ oyng, 2023), also in channels of distribution in tourism and leisure industry (Buhalis and Law, 2008;Law et al, 2014;Martin-Fuentes and Mellinas, 2018). Other areas experiencing changes in TIC, such as restaurant reservation, evolved similarly to bring a revolution to the tourism and food sectors (Ye et al, 2011;Law et al, 2014;Thompson, 2015;Quaglione et al, 2020;Nazmi et al, 2022;Nigro et al, 2023), via product acquisition for introducing channels of distribution in the digital space (Xiang et al, 2015;Angeloni and Rossi, 2021), and via using multiple devices (Palau-Saumell et al, 2019;Kamboj and Joshi, 2021;Zanetta et al, 2021;Sharma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For the last two decades, the field of technologies Information and Communication (TIC) advanced for opening a break-grounding change in business and management (Kraus et al. , 2022; Lau and Höyng, 2023), also in channels of distribution in tourism and leisure industry (Buhalis and Law, 2008; Law et al. , 2014; Martin-Fuentes and Mellinas, 2018).…”
Section: Introductionmentioning
confidence: 99%